2022
DOI: 10.1002/pc.26654
|View full text |Cite
|
Sign up to set email alerts
|

Progressive damage behavior of composite L‐stiffened structures with initial delamination defects under uniaxial compression: Experimental and numerical investigations

Abstract: L‐shaped stiffened composite panels inevitably produce delamination defects during manufacturing and service, which seriously affect the load‐bearing performance of the structure. In the present work, a combination of experimental and numerical simulations was used to investigate the effect of initial delamination defects with three different shapes (lossless, elliptical, and circular) in the skin on the axial compression properties of carbon fiber L‐shaped stiffened composite panels. Furthermore, to predict t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The micro‐cracking can result in laminate, which have nonlinear response for axial stress under compression load. In this paper, the lamina failure criterion and progressive damage nonlinear theory [ 66 ] were used to evaluate the CAI strength. Some studies showed that no uniform industrial agreement for failure criteria of laminated composite.…”
Section: Simulation Methodology and Modelmentioning
confidence: 99%
“…The micro‐cracking can result in laminate, which have nonlinear response for axial stress under compression load. In this paper, the lamina failure criterion and progressive damage nonlinear theory [ 66 ] were used to evaluate the CAI strength. Some studies showed that no uniform industrial agreement for failure criteria of laminated composite.…”
Section: Simulation Methodology and Modelmentioning
confidence: 99%
“…However, the manufacturing and use of CFRP components may result in certain defects, including delamination, fiber waviness, fiber breakage, and missing bundles. [1][2][3] To ensure the longevity of these components, various non-destructive testing (NDT) techniques have been developed, including ultrasonic testing, 4,5 eddy current testing (ECT), [6][7][8] pulsed eddy current (PEC) thermography, 9 infrared (IR) thermography, 9,10 x-ray tomography, 11 and microwave emission. 12 Among these methods, ECT is considered a vital NDT technique for CFRPs as it provides detailed information on the fiber distribution within the material.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, carbon fiber‐reinforced polymers (CFRPs) have gained popularity across the aerospace, automotive, and marine industries owing to their exceptional properties, such as low weight, high strength, and superior fatigue resistance compared to those of other materials. However, the manufacturing and use of CFRP components may result in certain defects, including delamination, fiber waviness, fiber breakage, and missing bundles 1–3 . To ensure the longevity of these components, various non‐destructive testing (NDT) techniques have been developed, including ultrasonic testing, 4,5 eddy current testing (ECT), 6–8 pulsed eddy current (PEC) thermography, 9 infrared (IR) thermography, 9,10 x‐ray tomography, 11 and microwave emission 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber reinforced polymer (CFRP) composites have been widely utilized in the field of the aviation industry as a consequence of their outstanding mechanical behaviors such as high strength/stiffness to weight ratio, high specific modulus and excellent fatigue resistance, and they are gradually replacing the conventional metallic materials like aluminum alloy to achieve the light-weight of the structure and enhance the maneuverability of the aircraft. [1][2][3][4][5] The composite stiffened panel, which is made up of the skin panel and the stiffener with a certain stacking sequence of the composite prepreg, [6,7] is one of the most common used structural components in the manufacturing process of the airplane, and it is going to sustain complicated loading conditions like axial compression during the process of the service, [8][9][10][11][12] which may directly trigger the emergence of the buckling. [13,14] However, these structural components are very vulnerable to the low velocity impact (LVI) loading while the airplane is flying.…”
Section: Introductionmentioning
confidence: 99%